Influence of Inclusion of Different Levels of Okara Meal in Replacement of Groundnut Cake in the Diet on Nutrient Utilization and Growth Performance in Japanese Quails - Mahto, D. K.; Sinha, A. K.; Sinha, S. K.; Shivani, Swati; Ranjan, Rajeev (Indian Journal of Animal Nutrition, 2017)
The present experiment was conducted to study the effect of inclusion of different dietary levels of okara meal (soybean byproduct) replacing groundnut cake in Japanese quail ration on nutrient utilization andgrowth performance for six weeks. Two hundred commercial one week old Japanese quail chicks were randomly divided into four treatments. Each treatment had 5 replicates with 10 chicks each. Ground nut cake was replaced by okara meal in ration at 0, 25, 50 and 75% on protein equivalent basis in treatments T1, T2, T3 and T4, respectively. Total feed consumption was similar in all the four groups. The average total weight was higher (P